China's counterterrorism measures: usefulness in engaging multilateral organisations - Yap, Dawn Yi Ning (Nanyang Technological University, 2025)
Although terrorism in China is typically framed as a domestic issue, high profile terrorist attacks against Chinese investments and citizens in foreign countries puts China’s counterterrorism strategies under the spotlight. Hence, this research project seeks to examine the usefulness of China’s involvement on multilateral platforms to address its counterterrorism measures. The two case studies are the Shanghai Cooperation Organisation as well as the Association of Southeast Asian Nations. It will be followed by a discussion of the factors for China’s choice to engage globally from the perspectives of domestic security, economic cooperation and desire to reshape the international security landscape. It concludes that China’s engagement on multilateral organisations builds a strong foundation for China to engage with member countries more effectively to execute their counterterrorism strategies.